Yet another iOS music player app - player++ V2 - Tan, Eunice Mei Jie (2017)
Technology and its continuous evolution have brought about tremendous changes in peoples’ lives as well as in every industry in the world. The concept of this project was conceived after market research on the top 20 music apps in the Apple App Store, with the aim of solving existing common problems. Among the listed tested apps, three main issues were identified, and these issues were the focus of this project. At the end, functions were implemented with the aim of solving the common problems. This project is a continuation of the project done by the previous Final Year Project student and with the development environment being updated every single year, it is impossible to continue work based on the previous development environment. Thus, this report will not only focus on the migration to a new development environment, debugging and the implementation of new functions on top of the ones already put in place will also be highlighted, all of which was done by the current Final Year Project student, Eunice Tan. Further direction and potential enhancements are also included in this project report for future versions and implementations.